A SIMPLE AND CONVENIENT SOLUTION FOR DATA ACQUISITION USING THE LABVIEW INTERFACE FOR ARDUINO VIA THE LINX MODULE - Tran Xuan Tien; Truong Dung Tuan (Journal of Applied Science and Technology, 2022)
This article focuses on utilizing the use of merging Labview software with Arduino via the LINX module in data acquisition from common sensors. First, a general overview of the process is offered with covering the connection between hardware components and software programs. The sensors’ data is sent into LabVIEW software through the Arduino board. The signal is processed, monitored, and recorded here. Following that, data acquisition programs from pressure sensors and ultrasonic sensors will be presented and evaluated in order to display and evaluate the data and visualization capabilities. The proposed solution is very suitable for small-scale applications with low-cost requirements in data acquisition.